Urban Land Markets Improving Land Management for Successful Urbanization - Lall, Somik V.; Freire, Mila; Yuen, Belinda; Rajack, Robin; Helluin, Jean-Jacques (Springer Netherlands : Imprint: Springer, 2009)
The challenge of facilitating economic density is fundamental for successful urbanization. Flexible and forward-looking institutions that help the efficient functioning of land markets are vital in this respect. In particular, institutional arrangements for regulating land use, managing public land and allocating land rights have significant implications for how cities deliver agglomeration economies and improve the welfare of their residents. This book provides fresh insights into these issues, compiling selected pieces of analytical and empirical research presented at the World Bank's Fourth Urban Research Symposium on Urban Land Use and Land Markets, held in Washington, DC, May 2007. Specially commissioned papers helped develop a robust analytical foundation to clarify ongoing debates on urban land management and welfare and synthesized the political and administrative challenges of improving the efficiency of urban land markets. Among the questions that this book addresses are: - Does more public intervention in land markets produce more affordable land market outcomes? - Do conventional approaches to strengthening property rights bolster security of tenure and market transactions? - How should governments go about integrating informal settlements with the broader city economy?